Increasing Added Value of Seaweed Products for Noodle and Jelly Candy in Petemon Surabaya - Dwi Yuli Pujiastuti; Mochammad Amin Alamsjah; Juni Triastuti (OJS Universitas Muhammadiyah Gresik, 2021)
In this PKM program, our partner is residents in Petemon, Surabaya, East Java Province. This community has generated the production of noodle and jelly candy from seaweed. Seaweed processing has a very broad market potential due to the increasing demand and use of seaweed processing products, whether used in the health, pharmaceutical or industrial fields. Development of seaweed with an industrial concept approach that starts from upstream, processing basic products into formulation products with a lot of derivative products, both food and non-food products. In food ingredients, seaweed can be formulated, among others, into ice cream, pudding, jelly candy or other foods and soft drinks Based on interviews and observations in the field, there are 2 main focuses of the problems currently faced by partners, namely: 1) lack of knowledge about seaweed and 2) product diversification of seaweed which have an added value. Some of the things planned by the PKM team are innovating seaweed to be noodle and jelly candy as well as providing training and mentoring for financial analysis, packaging and marketing. The purpose of this activity is to transfer knowledge of making product diversification of seaweed, develop the creativity of the partner, increase the noodle and jelly candy production and improve the welfare of the partner. This activity was realized with an approach in the form of making a sustainable cooperation program until the end of PKM, creating a family atmosphere between the two and understanding that the problems experienced were a shared problem so that they could be solved together according to the level of responsibility to achieve the expected benefits, namely increased yields, production and productivity and competitiveness, independence and welfare of the community.